2003
DOI: 10.2337/diacare.26.3.899
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetic Individuals Have Impaired Leg Blood Flow Responses to Exercise

Abstract: OBJECTIVE -Diabetic individuals have impaired endothelium-dependent forearm vasodilatory responses to ischemia, acetylcholine, and other endothelium-dependent agonists. The functional significance of impaired endothelium-dependent dilation in diabetic individuals is uncertain but is most likely to be manifest during leg muscle exercise and may have relevance to peripheral vascular disease and leg ischemia, which is prevalent in diabetic individuals. The current study aimed to determine the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
140
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(158 citation statements)
references
References 37 publications
(27 reference statements)
14
140
1
Order By: Relevance
“…2). Similar results were also found in patients with type 2 diabetes (14). Because previous studies have supported a critical role of prostaglandin(s) in mediating functional vasodilation (10,19,20,24,30), it is possible that the impaired functional vasodilation in metabolic syndrome may be due to altered AA metabolism.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…2). Similar results were also found in patients with type 2 diabetes (14). Because previous studies have supported a critical role of prostaglandin(s) in mediating functional vasodilation (10,19,20,24,30), it is possible that the impaired functional vasodilation in metabolic syndrome may be due to altered AA metabolism.…”
Section: Discussionsupporting
confidence: 76%
“…For example, SNP-induced dilation of isolated cerebral arteries was similar between 17-wk-old LZRs and OZRs (25). SNP-induced vasodilation was similar to controls for individuals with type 2 diabetes, although both ACh-induced and functional vasodilation were blunted (14). Previous studies have suggested that NO may not be important in mediating functional hyperemia (2,27,28,31).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Instead, the T2DM subjects achieved a smaller increase in cardiac output, despite having higher left ventricular stroke work during exercise. Vascular function is impaired in adults with T2DM (35,36) and ObeseND adolescents (37). Therefore, it appears that attenuated peripheral vasodilation during exercise, combined with a limited ability to increase cardiac contractility may have contributed to a smaller increase in cardiac output during steady-state exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes also presents a severe impairment of arterial (19,34) and microcirculatory (27, 28) hemodynamics in skeletal muscle at rest and during exercise. Key contributors to this condition are thought to include upregulation of endothelin-1 (37), prostaglandin (1), and myogenic (43) vasoconstrictor pathways combined with downregulation of vasodilatory endothelial function and nitric oxide bioavailability (17,24,48). Given the above, it is not surprising that the dynamics of Q O 2 , following exercise onset, for example, may be deficient as evidenced by the aberrant Pmv O 2 profile to muscle contractions, which reflects an imbalance between Q O 2 and V O 2 responses [type I (3); type 2 (28)].…”
mentioning
confidence: 99%